The Developing Model Of Distance Learning Programme Utilising Technology At Inland Water And Ferries Transport Polytechnic Of Palembang During Emergency Situatio - Sugiharto, Rudy (IWTJ : International Water Transport Journal, 2020)
Indonesia is one of state as the world’s biggest supplier of seafarers is being threatened by the growing share in the development of international seafarers by other countries in Eastern Europe and Asia, particularly China. The employability of seafarers depends largely on the quality of education they have acquired and the effectiveness of training that they have undergone pursuant to the requirements of STCW’95. If the country remains complacent about the present level of competence of its seafarers, it may lose out to other countries in the global labour market competition. The Philippines has to respond to the challenges in the global maritime environment by maintaining a viable supply of well-trained mariners. To achieve that, however, will require new approaches to maritime education and training. This new MET approach should be one that affords high quality output to a great number of seafarers. In other words, it must be something that meets both the quantitative and qualitative requirements of the industry and international regulatory authorities, particularly the IMO. This new approach to MET in the Philippines could be the establishment of a Distance Learning Programme. Distance learning employing state-of-the-art telecommunications technology, IT and satellite communications system will enable the Philippine MET to train a great number of seafarers even while they are at sea without sacrificing quality